Electrochromic Displays Screen Printed on Transparent Nanocellulose‐Based Substrates. Issue 1 (25th August 2022) - Andersson Ersman, Peter; Freitag, Kathrin; Nilsson, Marie; Åhlin, Jessica; Brooke, Robert; Nordgren, Niklas; Aulin, Christian; Fall, Andreas; Nevo, Yuval; Beni, Valerio
Abstract : Manufacturing of electronic devices via printing techniques is often considered to be an environmentally friendly approach, partially due to the efficient utilization of materials. Traditionally, printed electronic components (e.g., sensors, transistors, and displays) are relying on flexible substrates based on plastic materials; this is especially true in electronic display applications where, most of the times, a transparent carrier is required in order to enable presentation of the display content. However, plastic‐based substrates are often ruled out in end user scenarios striving toward sustainability. Paper substrates based on ordinary cellulose fibers can potentially replace plastic substrates, but the opaqueness limits the range of applications where they can be used. Herein, electrochromic displays that are manufactured, via screen printing, directly on state‐of‐the‐art fully transparent substrates based on nanocellulose are presented. Several different nanocellulose‐based substrates, based on either nanofibrillated or nanocrystalline cellulose, are manufactured and evaluated as substrates for the manufacturing of electrochromic displays, and the optical and electrical switching performances of the resulting display devices are reported and compared. The reported devices do not require the use of metals and/or transparent conductive oxides, thereby providing a sustainable all‐printed electrochromic display technology. Abstract : Transparent free‐standing nanocellulose‐based substrates are developed and subsequently utilized in the manufacturing of screen printed electrochromic displays. The optical and electrical switching performances are comparable with electrochromic displays screen printed on plastic substrates. In addition to this, neither metals nor transparent conductive oxides are required, thereby resulting in sustainable electrochromic displays relying on truly all‐organic materials, including also the substrate.